Fluctuations of crude oil and the impact on Malaysian oil producers - Izaan Jamil; Mori Kogid; Saizal Pinjaman; Debbra Toria Nipo; Thien Sang Lim; Jaratin Lily (Penerbit Universiti Malaysia Sabah, 2025)
This study aims to investigate the impact of price fluctuations of crude oil on oil producers’ companies in Malaysia. Individual stock prices of oil producers were selected instead of stock market indexes. This study employed an Autoregressive Distributed Lag Bounds (ARDL) model with weekly data spanning from January 2011 until June 2022. The empirical results found evidence of cointegration between crude oil and the stock price of PETRONAS Chemical, PETRONAS Gas, Hibiscus Petroleum and Petron Malaysia. This indicates that the stock prices move in tandem with crude oil towards long-run equilibrium. Furthermore, the study finds substantial statistical evidence of a causal impact from crude oil to the stock prices of oil producer companies, suggesting that Brent Futures significantly influences the stock price behavior of Malaysian oil producers. The empirical results of this study will be able to assist the fund managers of these oil producer companies or individual investors in designing investment strategies based on the price movement of crude oil.